2008
DOI: 10.1099/jmm.0.47518-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical parameters do not predict infection in patients with external ventricular drains: a retrospective observational study of daily cerebrospinal fluid analysis

Abstract: A retrospective review was conducted of patients with external ventricular drains (EVDs) in situ in order to ascertain the utility of daily cerebrospinal fluid (CSF) analysis in such patients. All laboratory requests for CSF analysis, which were sent to the Microbiology Department, Auckland City Hospital, New Zealand, were reviewed to identify patients with EVDs in situ. The patients' clinical records were reviewed and information was obtained regarding their age, ethnicity, indication for EVD, duration of EVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 12 publications
0
36
1
2
Order By: Relevance
“…(Hoefnagel et al, 2008;Kitchen et al, 2011;Korinek et al, 2005;Lwin, Low, Choy, Yeo & Chou, 2012;Muttaiyah et al, 2008;Pfisterer, Muhlbauer & Reinprechtet, 2003;Williams et al, 2011;Williamson et al, 2014).…”
Section: Resultsunclassified
See 4 more Smart Citations
“…(Hoefnagel et al, 2008;Kitchen et al, 2011;Korinek et al, 2005;Lwin, Low, Choy, Yeo & Chou, 2012;Muttaiyah et al, 2008;Pfisterer, Muhlbauer & Reinprechtet, 2003;Williams et al, 2011;Williamson et al, 2014).…”
Section: Resultsunclassified
“…Their prospective methodology tends to yield more accurate results given the ability to control certain points and variables. Pfisterer et al, (2003) concluded as did Muttaiyah et al, (2008) that patients were generally very unwell and unable to communicate signs and symptoms of an infection and therefore daily specimens were required. The focus of Pfisterer's et al, (2003) study was mainly looking at the association of drainage time and infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations